Kinematic analysis of devices with movable working body in the form of flat surface - Корчевский, Александр Николаевич (Technology audit and production reserves, 2014)
Kinematic analysis of the mechatronic system of fan-type separation devices - vibropneumatic separator and vibration concentration table, which are widely used for the separation of granular materials is presented. The purpose of the analysis is to obtain dependencies in the form of the deck motion equations for determining the pole velocity of the deck and its angular velocity, as well as angular acceleration of the deck, velocity and acceleration of any point of the deck. As a result of the studies, it is found that when changing the geometric parameters of the calculation scheme, it is possible to control the shape and motion kinematics of the working body - the deck. Modeling of kinematic parameters of the deck motion allows to estimate the distribution of the amplitude values of velocities and accelerations. Under the condition of finding the separated material on the working surface, it becomes possible to predict the state of the material bed in terms of looseness, “pseudo-density” of separation into enrichment products. In the production process cycles, known dependences allow to use them in configuring various technical models and influence technological efficiency.